Lecciones de vida para la mujer - Canfield, Jack, 1944-; Hansen, Mark Victor; Marston, Stephanie; Heredía, Rubén (Aguilar, 2007)
A collection of inspirational stories addresses the concerns and needs of women and offers step-by-step guidelines on how to build a better life, while covering such topics as finding time, balancing priorities, and making ends meet.